REGENERATIVE NEUROMA OF INJURED PERIPHERAL NERVE AFTER IMMEDIATE NERVE STUMP’S EPINEURIUM WELDING AND PARTIAL HINDLIMB IMMOBILIZATION - Molotkovets, V.; Tsymbaliuk, V.; Chaikovsky, Yu.; Korsak, A.; Likhodiievskyi, V. (World of Medicine and Biology, 2017)
The experimental model of operative intervention on injured peripheral nerve by immediate nerve stump’s epineurium welding and partial hindlimb immobilization was developed. We used neurohistological method for regenerative neuroma and distal nerve stump morphology assesment 5 mounth after surgical treatment. We revealed that sumultaneous usage of welding technique for nerve stumps coaptation both with partial hindlimb immobilization in postoperative period results in uniform maturation of connective tissue at neuroma site and more uniform neuroma site neurotization.
Keywords: peripheral nerve; epineural welding; partial hindlimb immobilization; regenerative neuroma